Investeringsbehoefte uitrusting wetenschappelijk onderzoek. A survey of future requriements for outfitting public scientific research in the Netherlands. Erik van de Linde, Erik Frinking, Andreas Ligtvoet. Fase 2 = Phase 2
Summary goes here